2004
DOI: 10.1148/radiol.2312020920
|View full text |Cite
|
Sign up to set email alerts
|

Infrarenal Aortic and Lower-Extremity Arterial Disease: Diagnostic Performance of Multi–Detector Row CT Angiography

Abstract: Multi-detector row CT angiography appears consistent and accurate in the assessment of patients with peripheral arterial occlusive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(131 citation statements)
references
References 23 publications
3
124
0
4
Order By: Relevance
“…There are studies in the literature showing an excellent concordance between the multislice CT and digital subtraction angiography (11)(12)(13). In our experience, CTA is a particularly useful initial diagnostic tool in iatrogenic complications, particularly in identifying the site of arterial injuries in patients with retroperitoneal hemorrhages.…”
Section: Discussionmentioning
confidence: 56%
“…There are studies in the literature showing an excellent concordance between the multislice CT and digital subtraction angiography (11)(12)(13). In our experience, CTA is a particularly useful initial diagnostic tool in iatrogenic complications, particularly in identifying the site of arterial injuries in patients with retroperitoneal hemorrhages.…”
Section: Discussionmentioning
confidence: 56%
“…Such a low proportion of consistency is clearly different from the results obtained by other authors. For CT scans, 97% sensitivity, 97% specificity, and 94% correctness were found in detection of significant lesions and occlusions (21,22). Most often interpretation errors and issues were related to assessments of normal vessel sections and detection of stenoses.…”
Section: A' B'mentioning
confidence: 99%
“…The study in this group that reported the highest sensitivity (99%), specificity (97%) and LR+ (37.1) and the lowest LR-(0.01) 26 was one of two studies that scored 12 out of 13 on the quality assessment, and reported recruiting an appropriate patient spectrum. The other high-quality study reported the next highest sensitivity (97%).…”
Section: Whole Legmentioning
confidence: 99%
“…26,38,54,[57][58][59][60] The full set of diagnostic accuracy results is presented in Table 8. All the studies presented the results on an arterial segment basis.…”
Section: Ctamentioning
confidence: 99%
See 1 more Smart Citation